An eye-tracking study on the effects of structured input and traditional instruction on the acquisition of English passive forms. Issue 2 (16th October 2020) - Benati, Alessandro
Abstract : The present study explores the effects of structured input and traditional instruction on the acquisition of English passive forms using online measurements (eye-tracking). Previous empirical research investigating the effects of processing instruction through offline measurements (sentence and discourse-level) has overall shown that it is an effective pedagogical intervention. Research investigating the main factor responsible for the effectiveness of processing instruction has confirmed that it is the structured input component that is the causative factor for the positive effects of processing instruction. The two main questions of this study are: (1) What are the effects of structured input and traditional instruction on accuracy when measured by an eye-tracking picture selection task? (2) Would possible differences in accuracy between structured input and traditional instruction be accompanied by changes in eye-movement patterns? To provide answers to the questions formulated in this study, one eye-tracking study was carried out. Sixty-four school-age learners (15–16 years old) participated and were assigned to one of two groups: structured input (n = 32 or traditional instruction (n = 32). Neither instructional group received explicit information. A pre- and post-training design was adopted and the two groups received two different instructional treatments (structured input vs traditional instruction). Participants were assessed through a picture selection eye-tracking task to measure accuracy and eye-movement patterns while they were processing auditory sentences. Results of the eye-tracking task indicated that the structured input group achieved significantly higher accuracy scores compared with  the group receiving traditional instruction. The main findings from the present study reveal that structured input training might cause a change in learners' eye-movement patterns.